PERHATIAN ORANG TUA TERHADAP KEINGINAN ANAK MASUK PERGURUAN TINGGI (STUDI SISWA KELAS XII SMA NEGERI 5 PEKANBARU) - Setiawan, Yongki Setiawan; Natuna, Daeng Ayub Natuna Ayub; Irja, Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Formulation of the problem in this study is how much the attention of parents towards child’s dream to entrance the college at SMA Negeri 5 Pekanbaru. The purpose of this study is determine the level of the attention of parents towards child’s dream to entrance the college at SMA Negeri 5 Pekanbaru. The benefits of this research can add insight into attention of parents towards child’s dream to entrance the college at SMA Negeri 5 Pekanbaru. This is a descriptive syudy with a quantitative approach. The populations are 384 students. The sample in this study used kuota sampling. The instrument used in this study was a questionnaire containing 64 items statement, the attention of parents towards child’s wish to entrance the college at SMA Negeri 5 Pekanbaru with indicators: (1) provision study facilties; (2) to help the child’s study activities; (3) to motivate child. From the research result show that the attention of parents towards child’s dream to entrance the college at SMA Negeri 5 Pekanbaru referred to this study is the attention of parent in high category. Key word: The attention of parent, child’s dream, entrance the college